Suture Anchor Repair of Quadriceps Tendon and Patellar Tendon Ruptures. Issue 2 (June 2019) - Huleatt, Joel; Gebrelul, Aaron; Premkumar, Ajay; Xerogeanes, John
Abstract : Purpose: To document patient-reported function, range of motion (ROM), and failure rate of a surgical technique for repairing quadriceps tendon (QT) and patellar tendon (PT) ruptures with suture anchors. Methods: Consecutive patients 18 years of age or older who had isolated QT or PT ruptures treated with suture anchor repair between 2004 and 2014 were identified. Patients were included if preoperative and minimum 6-month postoperative International Knee Documentation Committee (IKDC) scores and/or minimum 8-week postoperative ROM had been collected. The effects of patient age, interval between injury and surgery, and length of follow-up period on postoperative IKDC scores were analyzed with Pearson correlation. Results: QT repair was performed in 36 patients with a mean postoperative IKDC score of 66.9 and mean ROM of 0 to 116 degrees. PT repair was performed in 27 patients with a mean postoperative IKDC score of 64.4 and mean ROM of 0 to 117 degrees. The failure rate of the 63 suture anchor repairs was 4.8%. There was no significant correlation between IKDC score and either increasing age ( r =−0.23, P =0.15), increasing interval between injury and surgery ( r =0.12, P =0.46) or length of follow-up period ( r =0.07, P =0.67). No significant difference in IKDC score was found between knot-tied and knotless suture anchor repairs ( P =0.4). Conclusions: Suture anchor repair of QT and PT ruptures results in full active extension and a low failure rate, but IKDC scores indicate continued functional deficits in most patients. Level of Evidence: Level IV—therapeutic.